Geochemical, Biological, and Clumped Isotopologue Evidence for Substantial Microbial Methane Production Under Carbon Limitation in Serpentinites of the Samail Ophiolite, Oman. Issue 10 (22nd October 2021) - Nothaft, Daniel B.; Templeton, Alexis S.; Rhim, Jeemin H.; Wang, David T.; Labidi, Jabrane; Miller, Hannah M.; Boyd, Eric S.; Matter, Juerg M.; Ono, Shuhei; Young, Edward D.; Kopf, Sebastian H.; Kelemen, Peter B.; et al.
Abstract: In hyperalkaline ( pH > 10 ) fluids that have participated in low‐temperature (<150 ° C ) serpentinization reactions, the dominant form of C is often methane ( CH 4 ), but the origin of this CH 4 is uncertain. To assess CH 4 origin in serpentinite aquifers within the Samail Ophiolite, Oman, we determined fluid chemical compositions, analyzed taxonomic profiles of fluid‐hosted microbial communities, and measured isotopic compositions of hydrocarbon gases. We found that 16S rRNA gene sequences affiliated with methanogens were widespread in the aquifer. We measured clumped isotopologue ( CH 3 13 D and CH 2 12 D 2 ) relative abundances less than equilibrium, consistent with substantial microbial CH 4 production. Furthermore, we observed an inverse relationship between dissolved inorganic C concentrations and δ 13 C CH 4 across fluids bearing microbiological evidence of methanogenic activity, suggesting that the apparent C isotope effect of microbial methanogenesis is modulated by C availability. An additional source of CH 4 is evidenced by the presence of CH 4 ‐bearing fluid inclusions in the Samail Ophiolite and our measurement of high δ 13 C values of ethane and propane, which are similar to those reported in studies of CH 4 ‐rich inclusions in rocks from the oceanic lithosphere. In addition, we observed 16S rRNA gene sequences affiliated with aerobic methanotrophs and, in lower abundance, anaerobic methanotrophs, indicating that microbial consumption of CH 4 in the ophiolite may further enrich CH 4 in 13 C. We conclude that substantial microbial CH 4 is produced under varying degrees of C limitation and mixes with abiotic CH 4 released from fluid inclusions. This study lends insight into the functioning of microbial ecosystems supported by water/rock reactions. Plain Language Summary: Mantle rocks from beneath Earth's crust can be thrust to the surface, where they are exposed to rain and air containing carbon dioxide ( CO 2 ). The groundwaters that become stored in these rocks often contain methane ( CH 4, a major component of "natural gas"), which can be formed from carbon dioxide in the subsurface. To investigate these methane‐forming processes, we sampled water, gas, and suspended particles from groundwaters using wells previously drilled into the rocks. The particles contained microbes with the genetic ability to produce methane. We also precisely measured the amounts of combinations of C and H atoms of different masses (isotopes) in the natural gas to determine how it was formed. The results of these measurements suggest that microbes could actively produce a considerable amount of the methane, which mixes with methane from another source that was formed by non‐biological processes, possibly long ago under different conditions than today's. Rocks like those studied here are widespread in the Solar System, so our finding that microbes live and produce methane in these rocks could help guide the search for life beyond Earth. Key Points: 16S rRNA gene sequences affiliated with methanogens and CH4 clumped isotopologue compositions suggest substantial microbial CH4 production A second CH4 source, release of CH4 from fluid inclusions, is indicated by 13 C‐enriched ethane and propane C availability may influence the apparent C isotope effect of microbial methanogenesis